Activation of Parabrachial Tachykinin 1 Neurons Counteracts Some Behaviors Mediated by Parabrachial Calcitonin Gene-related Peptide Neurons. (1st May 2023) - Arthurs, Joe W.; Pauli, Jordan L.; Palmiter, Richard D.
Graphical abstract: Highlights: Activation of Tac1 PBN neurons promotes escape, not freezing. Activation of Tac1 PBN neurons does not elicit conditioned taste aversion (CTA). Activation of Tac1 PBN neurons blocks CTA generated by LiCl or CGRP PBN activation. Activation of Tac1+;CGRP− via INTRSECT replicates Tac1 PBN activation. Abstract: Many threats activate parabrachial neurons expressing calcitonin gene-related peptide (CGRP PBN ) which transmit alarm signals to forebrain regions. Most CGRP PBN neurons also express tachykinin 1 (Tac1), but there are also Tac1-expressing neurons in the PBN that do not express CGRP (Tac1+;CGRP− neurons). Chemogenetic or optogenetic activation of all Tac1 PBN neurons in mice elicited many physiological/behavioral responses resembling the activation of CGRP PBN neurons, e.g., anorexia, jumping on a hot plate, avoidance of photostimulation; however, two key responses opposed activation of CGRP PBN neurons. Activating Tac1 PBN neurons did not produce conditioned taste aversion and it elicited dynamic escape behaviors rather than freezing. Activating Tac1+;CGRP− neurons, using an intersectional genetic targeting approach, resembles activating all Tac1 PBN neurons. These results reveal that activation of Tac1+;CGRP− neurons can suppress some functions attributed to the CGRP PBN neurons, which provides a mechanism to bias behavioral responses to threats.